Characterisation of K-doped Bi4V2O11 by combined XRD and EPMA: a cautionary tale - Lee, Chnoong Kheng; Coats, Alison M.; West, Anthony Roy (International Centre for Diffraction Data, 1997)
A comparison of X-ray powder diffraction and electron probe microanalyses on samples of Na- and K-doped Bi4V2O11 (BIMEVOX) solid electrolytes indicates some of the problems associated with using XRD to assess phase purity, especially in materials of variable composition such as BIMEVOXes. In this study both the Na- and K-doped materials appeared phase pure by XRD. EPMA indicated the Na-doped materials to be single phase with their expected compositions while the K-containing materials were not phase pure with very little K present in the main BIMEVOX phase.